Identification and fine-mapping of a major QTL (PH1.1) conferring plant height in broomcorn millet (Panicum miliaceum) - Liu, Tianpeng; Liu, Xueying; He, Jihong; Dong, Kongjun; Pan, Wanxiang; Zhang, Lei; Ren, Ruiyu; Zhang, Zhengsheng; Yang, Tianyu (Frontiers in Plant Science, 2022)
The plant height of broomcorn millet (Panicum miliaceum) is a significant agronomic trait which is closely related to its plant architecture, lodging resistance, and final yield. However, genes underlying the regulation of plant height in broomcorn millet were rarely reported. Here, an F2 population derived from a cross between a normal variety “Longmi12” and a dwarf mutant “Zhang778” was constructed. The genetic analysis for the F2 and F2:3 populations revealed that the plant height was controlled by more than one locus. A major QTL, PH1.1, was preliminarily identified in chromosome 1 by bulked segregant analysis sequencing (BSA-Seq). PH1.1 was fine-mapped to a 109 kb genomic region with fifteen genes with a high-density map. Among them, longmi011482 and longmi011489 containing nonsynonymous variations in their coding regions, and longmi011496 covering multiple insertion/deletion sequences in promoter regions may be the possible candidate genes for PH1.1. Three diagnostic markers closely linked to PH1.1 were developed to validate the PH1.1 region in broomcorn millet germplasm. These findings laid the foundation for further understanding of the molecular mechanism of plant height regulation in broomcorn millet, and also are beneficial to the breeding program for developing new varieties with an optimal height.